Debate as a pedagogical tool to develop soft skills in EFL/ESL classroom: a qualitative case study - Aclan, Eunice M.; Abd Aziz, Noor Hashima; Valdez, N.P. (Universiti Putra Malaysia Press, 2016)
Soft skills development is seen as paramount in the 21st century knowledge economy but pedagogical tools to realise it are scanty.Thus, this study describes how debate, as a pedagogical tool with three stages (i.e., pre-debate, actual debate and post-debate), can develop the soft skills prescribed in the Malaysian Soft Skills Development Module (MSSDM).The key informants were five debate experts with debating experience and have taught All-Asians Parliamentary Debate (APD) for at least two years in the EFL/ ESL contexts in the ASEAN region.A semi-structured one-on-one interview was used to gather the data.To triangulate the debate experts’ perspective, a focus group interview was conducted with six classroom debate students from three ASEAN countries.The transcribed data were analysed using data analysis flow model where the data were condensed, sorted out, focused, organised and presented using the participants’ verbatim words. In the findings, the participants discussed how the pre-debate, the crucial foundation stage to outline the team’s case and arguments supported by evidences from rigid research, can develop all the soft skills in MSSDM, especially the teamwork and critical thinking and problem-solving skills. They also described how the actual debate, the most challenging stage because of the time limit in both speech and Point-of-Information, can develop soft skills, particularly quick critical thinking and effective communication skills.They also explained how the post-debate can develop the various soft skills by highlighting lifelong learning and information management and communication skills.From the findings, a debate pedagogical model to teach soft skills was developed.